2010
DOI: 10.1016/j.ijggc.2009.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Coupled reservoir-geomechanical analysis of CO2 injection and ground deformations at In Salah, Algeria

Abstract: In Salah Gas Project in Algeria has been injecting 0.5-1 million tonnes CO 2 per year over the past five years into a water-filled strata at a depth of about 1,800 to 1,900 m. Unlike most CO 2 storage sites, the permeability of the storage formation is relatively low and comparatively thin with a thickness of about 20 m. To ensure adequate CO 2 flow-rates across the low-permeability sand-face, the In Salah Gas Project decided to use long-reach (about 1 to 1.5 km) horizontal injection wells. In an ongoing resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
193
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 338 publications
(204 citation statements)
references
References 11 publications
5
193
0
6
Order By: Relevance
“…Simulation results showed that such ground uplift rate could be reproduced by considering pressure increase and volumetric expansion of both the injection zone and the overlying caprock (Rutqvist et al, 2010). This uplift rate would require the caprock permeability to be two orders of magnitude higher than the initially estimated value from core samples (Rutqvist et al, 2010). Furthermore, a double lobe uplift pattern appeared on top of KB-502 injection well, which was explained by the opening of a fracture zone at depth .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Simulation results showed that such ground uplift rate could be reproduced by considering pressure increase and volumetric expansion of both the injection zone and the overlying caprock (Rutqvist et al, 2010). This uplift rate would require the caprock permeability to be two orders of magnitude higher than the initially estimated value from core samples (Rutqvist et al, 2010). Furthermore, a double lobe uplift pattern appeared on top of KB-502 injection well, which was explained by the opening of a fracture zone at depth .…”
Section: Introductionmentioning
confidence: 90%
“…A ground uplift of around 5 mm/yr was measured on top of the three horizontal injection wells using satellite geodetic data (Vasco et al, 2008;Mathieson et al, 2009;Onuma and Okhawa, 2009). Simulation results showed that such ground uplift rate could be reproduced by considering pressure increase and volumetric expansion of both the injection zone and the overlying caprock (Rutqvist et al, 2010). This uplift rate would require the caprock permeability to be two orders of magnitude higher than the initially estimated value from core samples (Rutqvist et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…[7][8][9][10] Although these approaches can address the problem, significant efforts and costs are required to construct numerical models for each potential candidate site and for uncertainty studies of geometric, geological and material parameters. Analytical solutions or semianalytical approaches may be more suitable because of their computational efficiency and ability to identify driving mechanisms.…”
Section: J Nmentioning
confidence: 99%
“…5,6,28 Because highly accurate measurements are available, the surface heave at In Salah is considered an ideal benchmark problem for geomechanical modelling. Using these data, Rutqvist et al 8 and Preisig and Prévost 7 investigated the surface uplift around injection well KB501 using 3D and 2D numerical models, respectively. The results are in good agreement with the field measurements.…”
Section: Benchmark To the Case Of The In Salah Projectmentioning
confidence: 99%
See 1 more Smart Citation